Participants' perceptions of Computer-Mediated Communication: a case study of the Global Teenager Project - Turyagyenda, Joy Kyarimpa (Rhodes University, Faculty of Education, Department of Education, 2003)
The study outlines general trends evident in Computer-Mediated Communication (CMC), participants' perceptions and the promotion of CMC across the curriculum in a South African Secondary School. This case study focuses on the Global Teenager Project (GTP), which started as a bi-national pilot project in April 1999 between secondary schools in South Africa and the Netherlands. The study sets out to investigate how well the GTP can be incorporated into the existing school curriculum through the teacherresearcher's direct involvement in facilitating the project at a school where she is a fulltime teacher. The main purpose of the study is to review existing literature to establish how collaborative learning could be achieved through a CMC environment between teenagers from various countries based on the research done at an international level and link the practice at this school to the existing international trends. It was found that the GTP has great potential in enhancing collaborative learning within various learning areas at Nathaniel Nyaluza Secondary School (NNSS). Despite the usefulness of the GTP and the overwhelming enthusiasm learners displayed, its success at NNSS depended on the motivation of teachers and how easily the activities of the GTP could be incorporated within day-to-day teachers' activities.,Hodgkinson, Cheryl
Keywords: Global Teenager Project; Computer networks -- Social aspects; Communication; Telematics; Learning -- Technological innovations